ANALISIS KELAYAKAN AKSES DIFABILITAS DI PURI INDAH MALL - Satrya, Dandy; Melaina, Siska (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
This research report aims to analyze the feasibility of disabled access to public buildings (casestudy: Puri Indahmall kembangan south). The results of the study are expected to help improve thefeasibility of persons withdisabilities to engage in public buildings and for public buildings to apply standards to public buildings forpersons with disabilities. This study uses qualitative methods, with the regulation of the minister of public worksand architectural journals that are about accessibility as a benchmark of assessment. Data collection withobservation and feasibility rating using rating scale. The result of the study of the disability's effectiveness in thebeautiful castle mall valuation is good.